2013
DOI: 10.1080/03075079.2013.823931
|View full text |Cite
|
Sign up to set email alerts
|

External examining: fit for purpose?

Abstract: Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines.Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated otherwise on the metadata record) may be copied, displayed or performed, and stored in line with the JISC fair dealing guidelines (available here) for educational and not-for-profit activities provided that• the authors, title and full bibliographic detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…While the drive towards standardization across the system has resulted in a great deal of focus on the reliability, comparability, and transparency of procedures, far less attention has been paid to the quality of the underlying practice (Bloxham, 2009). As identified in the introduction, of the research that does exist, the findings do not inspire confidence and point to a system that is underpinned by largely unchallenged and unsupported assumptions (Bloxham and Price, 2015). One such assumption revolves around the assessment literacy of external examiners, which has provided the focus of this study.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…While the drive towards standardization across the system has resulted in a great deal of focus on the reliability, comparability, and transparency of procedures, far less attention has been paid to the quality of the underlying practice (Bloxham, 2009). As identified in the introduction, of the research that does exist, the findings do not inspire confidence and point to a system that is underpinned by largely unchallenged and unsupported assumptions (Bloxham and Price, 2015). One such assumption revolves around the assessment literacy of external examiners, which has provided the focus of this study.…”
Section: Resultsmentioning
confidence: 93%
“…The aim of this study is to evaluate the extent of assessment literacy demonstrated within the written reports of external examiners, thereby testing the validity of the unchallenged assumption of its presence within the external examining system (Bloxham and Price, 2015).…”
Section: Objectivementioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, both the concept and application of learning outcomes have received much attention in the literature (Bloxham and Price, 2013;QAA and HEA, 2013), with curriculum and assessment design being the main consideration and relatively less attention being given to how ILOs might actually connect with the practical issues involved in scoring students' individual achievement. However, interest in this issue is increasing in both the academic literature and the popular press.…”
Section: Ensuring Reliable Assessmentmentioning
confidence: 99%